Design and Implement an Exoskeleton Arm for Reinforcement the Human Muscles after Stroke - Abd-ul-Amir, Duha Qais; Hashim, Auns Qusai; Ameer, Abdulnasir Hussin (Al-Nahrain Journal for Engineering Sciences, 2019)
Mobility limitations in stroke survivors yield negative impacts on the quality of life for such individuals. Rehabilitation is needed to help them recover and regain mobility. Accordingly, this study aims to design and validate a “Robotic Exoskeleton” intended for stroke rehabilitation. The basic principles of this robotic exoskeleton device are its dependence on electromyography signal and electronic microcontroller to provide an efficient physiotherapy exercises system.The robotic exoskeleton is a one degree of freedom which performs the flexion and extension of the elbow joint. After the design was completed, 19 subjects participated in this study: 4 healthy subjects, and 15 post-stroke patients.The results showed the benefit of robotic exoskeleton in increasing the elbow range of motion, where angle of elbow flexion was raised from the first physiotherapy session to maximum elbow flexion in the last session.